2022
DOI: 10.9734/jalsi/2022/v25i530306
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Propensity of Africa Locust Bean (Parkia biglobosa) Seed on Lipid Profile against Potassium Bromate-induced Cardiotoxicity

Abstract: Background: Cardiovascular disease cases are on the increase despite many standard medical practices. Some disorders have been successfully treated by medicinal plants. Aim: The current study was designed to assess the chemotherapeutic propensity of Parkia biglobosa against potassium bromate-induced cardiotoxicity. Methodology: Using a soxhlet extractor with ethanol as the solvent, P. biglobosa was extracted. Twenty-four mature male Wistar rats were randomly divided into groups A, B, C, and D after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Phytate, tannin, oxyalate, and hydrogen cyanide are a few antinutritional components found in seeds [2]. The extract of African locust bean (ALB) is antibacterial [4], antidiabetic [7], antifungal [8], anti-inflammatory [9], anti-diarrheal [10], antihypertensive [11], hypoglycemia [12], hypolipidemic [13], and hepatoprotective [14] in addition to having many beneficial effects. A recent study by Ezirim et al [15] shown that ALB seed can alleviate testicular toxicity caused by potassium bromate.…”
Section: Introductionmentioning
confidence: 99%
“…Phytate, tannin, oxyalate, and hydrogen cyanide are a few antinutritional components found in seeds [2]. The extract of African locust bean (ALB) is antibacterial [4], antidiabetic [7], antifungal [8], anti-inflammatory [9], anti-diarrheal [10], antihypertensive [11], hypoglycemia [12], hypolipidemic [13], and hepatoprotective [14] in addition to having many beneficial effects. A recent study by Ezirim et al [15] shown that ALB seed can alleviate testicular toxicity caused by potassium bromate.…”
Section: Introductionmentioning
confidence: 99%
“…The higher lipid peroxidation in the kidney after As treatment may be caused by the formation of superoxide anion radical according to the decreased SOD activity in the kidney as shown in Figure 3 (160,161). When molecular oxygen interacts with the dimethyl arsine metabolite of dimethyl As acid, free radicals are produced.…”
Section: Mechanism Of Action Of Arsenic On Kidneymentioning
confidence: 99%
“…Humans who are acutely intoxicated with KBrO 3 can develop renal failure, neuropathological abnormalities, and thrombocytopenia, while those who are chronically intoxicated have been shown to develop a number of renal and nonrenal malignancies [5]. According to experimental studies, KBrO 3 can cause oxidative stress [6], hepatotoxicity [7], nephrotoxicity [8], testicular toxicity [9], dyslipidemia [10], lower sperm quality [11], decreased male reproductive hormones [12], abnormalities in coagulation factors [13], and other negative effects.…”
Section: Introductionmentioning
confidence: 99%